ANALISIS REALISASI ANGGARAN BELANJA LANGSUNG UNTUK MENILAI EFEKTIVITAS KINERJA PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA DAERAH (BKPSDMD) KOTA CIMAHI - CINDY WAHYUNI10 (JEBS (Journal of Economic and Business Student), 2023)
This study aims to determine how the direct expenditure budget realization is to assess the effectiveness of performance at the Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Daerah (BKPSDMD) of Cimahi City. The research method used is descriptive qualitative method. The data used is quantitative data. The results show that the development of the level of effectiveness of the financial management of the BKPSDMD for the 2017-2020 period is increasing every year. The highest level of effectiveness occurred in 2019 with a percentage of 89.74% and the lowest level of effectiveness occurred in 2017 with a percentage of 81,83%. Overall, it is included in the criteria of being quite effective, which is having an average effectiveness ratio of above 80%. There are several obstacles that occur, namely the decline in budget realization 2020 and changes in government policies. In dealing with these obstacles, the company’s efforts are made at the beginning of the budget, planning as well and optimally and conducting periodic evaluations